The Hydrogarnets Sr3[RE(OH)6]2 (RE = Sc, Y, Ho – Lu): Syntheses, Crystal Structures, and their Thermal Decomposition to Ternary Rare-Earth Metal Oxides - Albrecht, Ralf; Doert, Thomas; Ruck, Michael (Zeitschrift für Anorganische und Allgemeine Chemie, 2020)
Seven rare-earth metal hydrogarnets Sr3[RE(OH)6]2 (RE = Sc, Y, Ho-Lu) were synthesized at about 200 °C starting from the respective RE2O3 and Sr(NO3)2 in a KOH hydroflux with a water-to-base ratio of 1.6. All seven hydrogarnets crystallize in the acentric variant (space group I43d) of the cubic garnet structure. The crystal structures of the hydrogarnets Sr3[RE(OH)6]2, the differences between both structural variants including a simple method to distinguish between them, and the crystal-chemical classification with respect to other known strontium hydrogarnets are discussed. The rare-earth hydrogarnets can be used as carbon-free precursors for magnetic oxides. Starting at about 300 °C, the hydrogarnets decompose in a two- or three-step dehydration to SrRE2O4 and SrO. The decomposition of Sr3[Sc(OH)6]2 follows a different mechanism and was studied by in-situ temperature-dependent powder X-ray diffraction up to 1000 °C. The final decomposition products were SrO and an unknown strontium scandium oxide, with an X-ray pattern similar to BaSc2O4. Magnetic measurements of the erbium and ytterbium hydrogarnets revealed paramagnetic behavior down to 1.8 K.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Hydrogarnet; Structure elucidation; Thermal decomposition; Rare earth compounds; Hydroflux